National Webinar on Philosophy and Psychological Review of Thinking Disposition - Yayan Eryk Setiawan; Triwilujeng Ayuningtyas (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Abstract In addition to the ability to think, students need a thinking disposition to succeed in learning. However, the results of preliminary research indicate that the knowledge of prospective teachers, teachers, and lecturers is still low on thinking dispositions. Therefore, this problem can be solved by conducting a national webinar on dispositions of thinking. Thus, the purpose of this service is to provide participants with an understanding of the philosophical and psychological dispositions of thinking. This service method is in the form of a national webinar, which is a seminar held online. This webinar activity is divided into three stages, namely the material presentation stage, the question and answer stage, and the community service evaluation stage. The results of this community service evaluation show that the percentage of the results of filling out the questionnaire is 81% which means that it is in the very high category. This means that this national webinar activity was very successful in understanding the participants towards a philosophical and psychological review of thinking dispositions. This success is supported by the availability of material, internet signals, and the ability of the presenters to convey the material. Apart from that, there are also inhibiting factors in this seminar activity, namely inadequate material delivery time, signal constraints, and too many presenters.